2021
DOI: 10.3390/ani11051273
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Alfalfa with Paper Mulberry in Total Mixed Ration Silages: Effects on Ensiling Characteristics, Protein Degradation, and In Vitro Digestibility

Abstract: To develop an alternative high-protein forage resource to alleviate ruminant feed shortages, we investigated the effects of replacing alfalfa (Medicago sativa L.) with different ratios of paper mulberry (Broussonetia papyrifera L., RY) on fermentation quality, protein degradation, and in vitro digestibility of total mixed ration (TMR) silage. The TMR were made with alfalfa and RY mixtures (36.0%), maize meal (35.0%), oat grass (10.0%), soybean meal (7.5%), brewers’ grain (5.0%), wheat bran (5.0%), premix (1.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It was found that PMS would lead to a lower TVFA in rumen before slaughter. This may be due to the high digestibility of PMS, which can pass through rumen faster [11]. In all treatments, the rumen TVFA content decreased after 12 h of fasting.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It was found that PMS would lead to a lower TVFA in rumen before slaughter. This may be due to the high digestibility of PMS, which can pass through rumen faster [11]. In all treatments, the rumen TVFA content decreased after 12 h of fasting.…”
Section: Discussionmentioning
confidence: 87%
“…Evidence supports the effect of tannin's regulation of rumen lipid metabolism on meat polyunsaturated fatty acids (PUFA) [8]. Based on this, paper mulberry may have the potential to reduce rumen BH and improve meat quality because of the high concentration of condensed tannin [11]. It seems that the reasons for these different observations are not clear yet, and the underlying lipids metabolism mechanism of rumen needs to be clarified in the future study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results were consistent with the research data of Dong et al [ 9 ]. It was found that different mixing proportion of silage materials would significantly affect the fermentation lignocellulose characteristics, especially for the content of neutral detergent fiber and acid detergent lignin [ 35 ]. This study found that compared with other mixing ratios, there were greater degradation rates of hemicellulose (27.27%) and neutral detergent fiber (19.06%) in BP65.…”
Section: Resultsmentioning
confidence: 99%
“…Hybrid Broussonetia papyrifera has the advantages of strong stress resistance and high resistance to diseases and insect pests. The leaves of hybrid B. papyrifera have a high protein content of which exceeds 20% and can be used directly as livestock feeds or as a raw material for a total mixed ration (TMR) ( 21 ). Now, by making hybrid B. papyrifera fermented feed, it can not only preserve a large amount of vitamins, but also make it taste sour, sweet and mellow ( 22 ).…”
Section: Introductionmentioning
confidence: 99%